The Impact of Evolving Algorithms on Search Engine Optimization Strategies - Mukherjee, Debmalya; Nath, Shuvrajit; Prasad Mitra, Shankar; Banerjee, Ranjan; Nayak, Partha Shankar (Journal of Neonatal Surgery, 2025)
Strategies aimed at improving website visibility in search engine results, known as Search Engine Optimization (SEO), are commonly employed. However, the proliferation of internet-based malware has created new avenues for cybercriminals. In addition to conventional methods like malicious links or attachments in unsolicited emails, attackers are increasingly utilizing sophisticated tactics. A particularly concerning trend is the exploitation of search engines to distribute malware, which can have significant consequences. This approach, termed SEO poisoning, manipulates search results for popular search terms, spreading malware effectively. While a relatively recent phenomenon, it has proven to be both pervasive and impactful, often involving the compromise of legitimate websites and the creation of numerous fake pages targeting trending keywords